Physical activity towards health & fitness 4 (PATH-FIT 4) : menu of sports - Punzalan, Michelle D.; Habana, Antonio Jardin Jr.; Pineda, Mercy D. (Manila : Mindshapers Co. , Inc., 2024)
"Sport is an activity that involves physical exertion and skill as its main focus with elements of competition where rules are strictly followed either for enjoyment and/or as a job. This book is prepared in accordance with the course PATH-FIT 4 (Physical Activities Toward Health and Fitness-Menu of Sports). It includes review of sport skills, sports management, as well as activities focusing on badminton, volleyball and basketball. This book is divided into four chapters. Students will be able to learn the basic skills, the equipment used, and the rules of the game of badminton, volleyball and basketball. It involves mastery and refinement of sports skills essential to adopt an active lifestyle, and lifelong health."
Includes references.
English
Keywords: Physical education--Sports